Hubungan Frekuensi dan Lama Merokok terhadap Kadar Hemoglobin (Hb) pada Perokok Aktif di Pasar VI, Kelurahan Binjai Utara - Ari Nurhasanah; Suharsih Suharsih; Junaidi Parinduri (Pusat Riset dan Inovasi Nasional, 2026)
Smoking is the activity of smoking smoke from the burning of tobacco in cigarettes, one end of the cigarette is burned and the smoke can be smoked through the mouth on the other end. If the amount or form of hemoglobin is abnormal, red blood cells cannot function properly in transporting oxygen and carbon dioxide. This can trigger various health problems, including anemia. From the results of this study, we can see that the average value or mean value of hemoglobin levels is 12.5 g/dL, the median value is 12.9 g/dL, the minimum value is 11.9 g/dL, and the maximum value is 16.2 g/dL. The results showed that most of the respondents had hemoglobin levels within normal limits. In detail, hemoglobin levels in the normal category were 23 respondents, low category was 1 respondent, and high category was 1 respondent. This shows that the majority of active smokers in Market VI of North Binjai Village still have normal hemoglobin levels, although smoking has the potential to affect oxygen transport capacity in the long term and increase the risk of health problems if it continues continuously.